Evaluation of the therapeutic results of actinic keratosis treated with topical 5% fluorouracil by reflectance confocal laser microscopy: preliminary study - Priscila Ishioka; Marcus Maia; Sarita Bartholomei Rodrigues; Alessandra Cristina Marta; Sérgio Henrique Hirata (Sociedade Brasileira de Dermatologia, 2015)
Abstract Topical treatment for actinic keratosis with 5% fluorouracil has a recurrence rate of 54% in 12 months of follow-up. This study analyzed thirteen actinic keratoses on the upper limbs through confocal microscopy, at the time of clinical diagnosis and after 4 weeks of treatment with fluorouracil. After the treatment was established and evidence of clinical cure was achieved, in two of the nine actinic keratoses, confocal microscopy enabled visualization of focal areas of atypical honeycomb pattern in the epidermis indicating therapeutic failure. Preliminary data suggest the use of confocal microscopy as a tool for diagnosis and therapeutic control of actinic keratosis.